Banking behaviour of expatriate lecturers in Singapore. - Goh, Amy. (2013)
The competitive banking environment today forces banking institutions to continuously seek out profitable market segments. With the regionalisation of the Singapore’s economy, the growing number of expatriates forms a ready market for these institutions. In order to give a better insight of this market niche, a study on the banking behaviour of the expatriate lecturers in Singapore is initiated.